Komodifikasi Kedukaan Keluarga Brigadir J Dalam Talk Show Rosi di Kompas TV - Bonardo Marulitua Aritonang (Brand Communication, 2023)
Television as an agent of capitalism produces a variety of programs that are able to "deceive" the interest of its viewers. Not only as a product of technology, television has been transformed into an instrument that allows the wide distribution of values and meanings. The meaning of grief has transformed into a major commodity. Even grief is often used as a commodity that is manipulated so that the storyline becomes more somber and dramatic so that it can grab public attention. In false consciousness, we are brought in and perceive media reality as real life reality as represented in the talk show ROSI on Kompas TV which displays grief in Rosti Simanjuntak and Vera Simanjuntak as the family of the late Brigadier J. This research intends to uncover the practice of commodification of grief packaged into a talk show ROSI on Kompas TV, including describing the consensus on the meaning of grief itself. By using the Commodification Theory and qualitative research method with Roland Barthes' semiotic approach, the researcher found that with audio and visuals that penetrate the public mind quickly and continuously, making viewers no longer able to reflect on the television programs they watch. This is what makes them easily take for granted the knowledge of social values about the topics they witness, including the practice of commodification and consensus on the meaning of grief. Through television shows, the production team of the talk show ROSI on Kompas TV has labeled grief as a "creature" that should be pitied, has a weak condition, depends on others so that it must be helped and quarantined. Labeling of grief experiences stabilization or perpetuation of meaning. Even the consensus on the meaning of grief in the ROSI talk show program on Kompas TV with the title "Joshua's Mother: No Word of Surrender!" episode September 22, 2022, actually became the savior for capitalists who are always thirsty for profit gratification.